2005
DOI: 10.1039/b408851d
|View full text |Cite
|
Sign up to set email alerts
|

2,5-Dimethylphenacyl carbonates: A photoremovable protecting group for alcohols and phenols

Abstract: Synthesis and photochemistry of a photochemically removable protecting group for alcohols and phenols, based on the 2,5-dimethylphenacyl (DMP) chromophore, is described. DMP carbonates release the corresponding hydroxy group containing molecules in high isolated yields (>70%), with quantum yields Phi= 0.1-0.2 in methanol and Phi= 0.36-0.51 in cyclohexane. The reactions proceed predominantly by the triplet pathway via E-photoenols, the lifetimes of which of approximately 2 s or 3 ms in cyclohexane or methanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 24 publications
5
51
0
Order By: Relevance
“…Microwave energy has exhibited its great ability to accelerate reactions and to improve yields and selectivity on synthetic organic chemistry [2]. Recently, microwave irradiation has been used to assist photochemical reactions in the degradation of organic pollutants [3][4][5][6][7][8][9][10]. The results of these experiments showed that microwave irradiation could considerably accelerate the photodegradation of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave energy has exhibited its great ability to accelerate reactions and to improve yields and selectivity on synthetic organic chemistry [2]. Recently, microwave irradiation has been used to assist photochemical reactions in the degradation of organic pollutants [3][4][5][6][7][8][9][10]. The results of these experiments showed that microwave irradiation could considerably accelerate the photodegradation of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Horihoshi et al [10] considered that specific interactions of the microwave radiation with the UV-illuminated TiO 2 particle surface may give rise to the generation of additional surface defects that can directly increase the concentration of hydroxyl radicals or some other but equivalent reactive oxygen species in the aqueous dispersion. Moreover, chemical processes performed under microwave radiation are believed to be affected by superheating, polarization, dielectric properties, hot spots formation, nuclear spin rotation, and spin alignment [15]. On the other hand, microwave enhances the reactants mobility and diffusion leading to increased exchange of reactants between catalyst surface and solution.…”
Section: Effect Of Initial Concentration Of X-3bmentioning
confidence: 99%
“…The problem will be solved if microwave electrodeless lamp (MWL) substitutes traditional lamp as light source. Moreover, MWL has some unique advantages, such as, good photochemical efficiency, long life, low cost, and simple photocatalytic equipment [14,15]. The light intensity can be adjusted by variations of MW power level and irradiation wavelengths can be adjusted by the ratio and nature of the gases in electrodeless lamp [8].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in using microwave radiation to drive or otherwise assist chemical reactions. Various types of organic and inorganic reactions, once performed using classical heating methods, are now routinely performed using microwave radiation [10]. Recently, researches have been conducted actively to improve oxidative degradation performance by adding microwave irradiation as an effort to utilize TiO 2 photo-catalyst treatment more efficiently [11][12][13].…”
Section: Introductionmentioning
confidence: 99%